Analysis on Factors that Influence Job Satisfaction of Government Employees - Kadarisman, Muh (UI Scholars Hub, 2013)
This research discusses how far job satisfaction is achieved, the factors that influence job satisfaction, and what needs to be done in order to increase the job satisfaction of Government Employees working at the Bogor Regency Secretariat. The objective of this research is to analyze the level of job satisfaction and the factors that influence job satisfaction, plus recommend what can be done to increase job satisfaction of Government Employees working at the Bogor Regency Secretariat. A criteria range analysis (analisis rentang kriteria) method was used to determine the level of job satisfaction of Government Employees. Results revealed that Government Employees were at a satisfied scale. The results from this research were obtained by using a factor analysis method to analyze the factors of job satisfaction of Government Employees. Eleven dominant factors were the reasons why Government Employees were satisfied with their jobs. These factors include: 1. Salary; 2. Benefits and facilities; 3. Relationship between superiors and subordinates; 4. Relationship among coworkers; 5. Development; 6. Opportunity; 7. Safety at work; 8. Education; 9. Policies within the organization; 10. Conflict resolution; and 11. Career achievements. The results of this research can be used as a suggestion for organization managements to improve the job satisfaction of Government Employees. The management can focus their attention on improving employee job satisfaction by referring to the eleven dominant factors in order to become more efficient and effective in making policies and be able to focus on the improving these job satisfaction factors.